Experimental investigation on water release and gas emission of evapotranspirative capillary barrier landfill covers. Issue 2 (7th February 2022) - Chen, Rui; Huang, Junwen; Leung, Anthony Kwan; Chen, Zhongkui; Chen, Zibin
Abstract: Evapotranspirative (ET) landfill covers release soil moisture stored therein by grass root–water uptake during the drying process. The reduction of soil water content during this process, however, would cause an increase in gas permeability and landfill gas emission. Few studies have focused on the mechanisms of water release and gas emission in ET covers under drying conditions and how different cover configurations might affect the water–gas transport mechanisms. In this study, a series of soil column tests were conducted to investigate the water and gas transport in three configurations of ET covers, namely monolithic cover, two‐layer capillary barrier cover (CBC), and three‐layer CBC. All columns were subjected to the same drying treatment for 42 h followed by the application of a constant gas pressure at the column base. Vertical distributions of pore water pressure, volumetric water content, and pore gas pressure, as well as any gas emission rate from the top of each cover were measured. Compared with the monolithic ET cover, the two‐layer capillary barrier ET cover did not adversely affect the cumulative amount of water release, but the presence of the coarse‐grained layer, which has relatively high gas permeability, caused a higher gas emission rate. In the three‐layer cover, the addition of a low‐permeability layer underneath the capillary barrier effectively minimized gas emission. On the other hand, the upper two‐layer capillary barrier can avoid desiccation cracks of the low‐permeability layer during the drying period. Core Ideas: The water‐release capacity of three ET landfill covers was similar. The presence of a coarse‐grained layer in the ET covers caused a higher gas emission rate. The addition of a low‐permeability layer to the ET covers effectively minimized gas emission.